(untitled) (TERRA LATINOAMERICANA, 2025)
In seed production, it is necessary to determine the response of single crosses that serve as parents of three-way hybrids under conditions of limited water availability. The objective of this research was to determine water use ef ficiency and agronomic variables of three single-cross maize hybrids (IA442 F × IA446, IA424 F × IA249, IA442 F × IA213), parents of three-way hybrids, under tassel and leaf elimination treatments. The experiments were conducted in two locations in the Valley of Mexico, Cuautitlán and Texcoco, State of Mexico. The three hybrids were evaluated under the following treatments: without detasseling (control), detasseling (D), and detasseling with removal of one to five leaves (D+1, D+2, D+3, D+4, D+5). A factorial experiment was established using a randomized complete block design with three replications. Total water use ef ficiency and grain yield showed significant dif ferences between environments (p < 0.05): 2.2 kg m–³ and 9.98 Mg ha–¹ in Cuautitlán, and 0.9 kg m–³ and 6.39 Mg ha–¹ in Texcoco. Significant dif ferences were also observed among crosses, with values of 1.5 kg m–³ and 7.8 Mg ha–¹ for IA442 F × IA446; 1.3 kg m–³ and 6.87 Mg ha–¹ for IA424 F × IA249; and 1.9 kg m–³ and 9.99 Mg ha–¹ for IA442 F × IA213. The detasseling and leaf-removal treatments produced a significant ef fect only on ear length; however, tassel removal alone resulted in higher water use ef ficiency and grain yield (1.7 kg m–³ and 9.05 Mg ha–¹). The IA442 F × IA213 genotype showed the highest water use ef ficiency, reaching 2.7 kg m–³ under limited water conditions (Cuautitlán). No ef fect of detasseling or leaf removal on total water use ef ficiency was observed.